Manajemen Sumber Daya Manusia dalam Retail: Peran Pelatihan dan Motivasi Karyawan dalam Meningkatkan Penjualan - Adrian Mjesfa (STIKes Ibnu Sina Ajibarang, 2025)
The purpose of this study is to determine the relationship between human resource management, training, and motivation in increasing sales in the retail sector. This study uses a qualitative approach with a Case Study method in 5 Retail Stores in West Nabire District, Nabire Regency, Central Papua Province. The research location is in Nabire District, Nabire Regency, Central Papua Province which was conducted for 1 month, namely from February to March 2025. The method of collecting informants was carried out using the Snowball method and obtained informants as many as 72 store employees from 5 retail stores. The data collection technique was carried out using the Triangulation method, namely Observation, Interviews, and Documentation. Data analysis was carried out by organizing data, sorting into one manageable data, synthesizing, searching and finding patterns, finding important things that can be learned, and systematically compiling data obtained from interviews, field notes, and research documentation conducted. The results of the study show that: (a). The average level of employee education is high school. (b). Employee motivation in increasing sales in the retail business is not always influenced by training factors. (c). Employee motivation to increase sales depends on employee comfort in the workplace (environment, bonuses, incentives, and fairness in employee performance appraisals).